2009
DOI: 10.3923/pjbs.2009.1468.1473
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Z and Protein C in Neonates with Respiratory Distress Syndrome in Egypt (Experience of One Centre)

Abstract: The aim of this study is to evaluate Protein Z (PTZ) and protein C (PTC) levels in newborns suffering from RDS, healthy preterm and full term newborns and to compare PTZ serum levels in RDS preterm infants with healthy preterm before and after recovery. Sixty newborn infants, recruited from the neonatal unit, were enrolled in the study and divided into 3 groups: Group (I): 20 preterm with RDS, Group (II): 20 healthy preterm control newborns (CPT) and Group (III): 20 healthy full term control newborns (CFT). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…This was in agreement with other researchers (16) who showed no effect of weight, APGAR score, hemoglobin %, TLCs on PTZ levels. Also, our results were in agreement with other researchers (21) , who noted no effect of weight on PTZ levels.…”
Section: Fibrin Deposition Has Been Demonstratedsupporting
confidence: 94%
See 1 more Smart Citation
“…This was in agreement with other researchers (16) who showed no effect of weight, APGAR score, hemoglobin %, TLCs on PTZ levels. Also, our results were in agreement with other researchers (21) , who noted no effect of weight on PTZ levels.…”
Section: Fibrin Deposition Has Been Demonstratedsupporting
confidence: 94%
“…They suggested that the reduction of PZ in RDS may contribute to the prothrombotic condition. Our results also were in agreement with the results of a study done by other researchers(16) who found lower levels of protein Z (PZ) in newborns suffering from RDS than in healthy newborns.…”
supporting
confidence: 93%